Відповідь:
1 - Г; 2 - В; 3 - Д; 4 - Б
Пояснення:
1) 4(x-y)^2 - 9y^2 за формулою різниці квадратів це дорівнює:
(2x-2y-3y)(2x-2y+3y) = (2x-5y)*(2x+y) а це варіант Г
2) 4(x-y)^2 - 9x^2 = (2y-2x-3x)*(2y-2x+3x) = (2y-5x) * (2y+x) (варіант в)
3) (3x-3y-2y)*(3x-3y+2y) = (3x-5y)*(3x-y) (варіант д)
4) (3x - 3y -2x) * (3x-3y +2x) = (x-3y) * (5x-3y) (варіант Б)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
1 - Г; 2 - В; 3 - Д; 4 - Б
Пояснення:
1) 4(x-y)^2 - 9y^2 за формулою різниці квадратів це дорівнює:
(2x-2y-3y)(2x-2y+3y) = (2x-5y)*(2x+y) а це варіант Г
2) 4(x-y)^2 - 9x^2 = (2y-2x-3x)*(2y-2x+3x) = (2y-5x) * (2y+x) (варіант в)
3) (3x-3y-2y)*(3x-3y+2y) = (3x-5y)*(3x-y) (варіант д)
4) (3x - 3y -2x) * (3x-3y +2x) = (x-3y) * (5x-3y) (варіант Б)